Strong Interaction between Cyclo[18]Carbon and Graphene. Issue 5 (26th March 2021) - Chen, Jialu L.; Zhang, Ruiqin Q.
Abstract: The recent observation of cyclo[18]carbon by atomic force microscopy has attracted wide interest. Its electronic structures, adsorption of small molecules, π–π stacking interaction, and doping properties have been studied by theoretical calculations. Interaction of cyclo[18]carbon with another allotrope graphene will be worthwhile for understanding weak interaction. Some researchers have performed the adsorption energy calculations of the carbon ring on graphene but obtained an incorrect structure. Therefore, accurate calculations for the system are still necessary. In the work, the system is optimized with periodic and nonperiodic methods. Additionally, several wavefunction analyses and molecular dynamics simulations are also performed for the system. Large adsorption energy is ensured, and graphene can be used to isolate C18 molecules. Abstract : A systematical research is conducted about interaction between cyclo[18]carbon and graphene by density function theory. Large adsorption energy is ensured, and graphene can be used to isolate C18 molecules.